Numerical Analysis of Fluid Flow Characteristics inside Micro Channel - Jugal Kumar, Sahu; Rashmi, Ray (International Journal of Engineering and Technology, 2018)
In accordance to the advancement in the field of technology, modern society has privilege to have access to multifunctional devices. Indeed, the life has become surprisingly easier than preceding era, where as it brings its own consequence in terms several life-threatening diseases due to lack of physical activity. One of the most oozing out concern of the world is heart disease facilitated by cholesterol deposition in the arteries. In preceding years several researchers have put enormous effort to deepen understanding of this disease. Here in this study, computational fluid dynamics based finite element method commercial software COMSOL is used for numerical simulation of blood flow through the stenosed artery. The incompressible Navier Stokes equation is used for modeling blood flow in constricted channel. The blood is modeled as non-Newtonian fluid with the help of Carreau model. Various shape of constricted channel is considered to depict several biological occurrences of the blockage. Wide range of parameters such as blockage ratio (B = 10-50%), blood viscosity and blood velocity are evaluated to explore the phenomena of flow skewness and to explore the recirculation phenomena in the blood flow stream past partially blocked artery.Â Â